2016
DOI: 10.1016/j.bbacli.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum omentin-1 levels in patients with pancreatic adenocarcinoma

Abstract: BackgroundOmentin is related with metabolic syndrome and obesity. Pancreatic adenocarcinoma (PA) is a lethal and obesity-linked malignancy. This study was conducted to investigate the serum levels of omentin in patients with PA and the relationship with tumor progression and known prognostic parameters.Material and methodsSerum samples were obtained from thirty-three patients on first admission before any treatment. Age, sex and body mass index (BMI) matched 30 healthy controls were included in the analysis. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
(20 reference statements)
2
17
0
2
Order By: Relevance
“…The role of omentin-1, an important adipokine produced by adipose tissue, is controversial in various cancers. [19][20][21] Studies showed that the serum level of omentin-1 is elevated in chronic and acute pancreatitis, prostate and colorectal cancer, while it is decreased in patients with breast, bladder and renal cell cancers. 21,34,35 The results of studies suggest that omentin-1 may play different roles in tumorigenesis and anti-oncogenic pathways in cancer.…”
Section: Serum Omentin-1 Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of omentin-1, an important adipokine produced by adipose tissue, is controversial in various cancers. [19][20][21] Studies showed that the serum level of omentin-1 is elevated in chronic and acute pancreatitis, prostate and colorectal cancer, while it is decreased in patients with breast, bladder and renal cell cancers. 21,34,35 The results of studies suggest that omentin-1 may play different roles in tumorigenesis and anti-oncogenic pathways in cancer.…”
Section: Serum Omentin-1 Levelsmentioning
confidence: 99%
“…18 Researchers showed that the serum level of omentin-1 is elevated in chronic and acute pancreatitis, while it is decreased in patients with polycystic ovary syndrome and BC. [19][20][21] Genetics studies have demonstrated that there are significant relationships between omentin-1 109Asp/Val genotypes and BC risk. 22 Despite all the available data, there is no evidence for the association of omentin-1 with oxidative stress and clinical significance in patients with BC.…”
Section: Introductionmentioning
confidence: 99%
“…Higher adipokine concentrations have also been detected in patients with pancreatic adenocarcinoma, with a positive correlation found between an increase in its concentration and tumour mass. Such observations may suggest the use of the protein in screening tests for early cancer detection [24][25][26][27]. Omentin is also attracting a growing interest in the context of the development of cardiovascular diseases.…”
Section: Omentynamentioning
confidence: 99%
“…Większe stężenie adipokiny stwierdzono także u chorych z gruczolakorakiem trzustki, a wzrost jej stężenia dodatnio korelował z masą guza. Obserwacje te mogą sugerować wykorzystanie tego białka w badaniach przesiewowych w kierunku wczesnego wykrycia nowotworów [24][25][26][27]. Omentyna wzbudza coraz większe zainteresowanie w związku z choro-Dermatology Review/Przegląd Dermatologiczny 2017/5 lium, halting oxidative stress and inflammation through TNF-α inhibition, suppression of monocyte adhesion to endothelial cells by inhibiting the expression of ICAM-1 and VCAM-1 [28,29].…”
Section: Omentynaunclassified
“…Pomiaru stężenia omentyny-1 we krwi dokonywano przed rozpoczęciem leczenia. Jej stężenie było wyższe u pacjentów z gruczolakorakiem trzustki niż u pacjentów zdrowych i było wyższe u pacjentów z guzem o większych rozmiarach niż u pacjentów z guzem małej wielkości [33].…”
Section: Zastosowanie Omentyny Jako Biomerkera W Medycynieunclassified